Juridical Implication of the Legal Vacuum in Providing Compensation in Lieu of Restitution - Ryan Ilham Fibriansyah; Nurini Aprilianda; Nadzriah Ahmad (Trunojoyo Madura University, 2025)
Criminal offenses position victims as aggrieved parties affected by crimes committed against them. The protection and recovery measures for the losses victims bear should guarantee justice, ensuring victims receive compensation for the harm caused. Law No. 1 of 2023 concerning the Indonesian Penal Code implies that compensation is an additional punishment imposed on the defendant. However, imprisonment, supervision, or community service are only applied if the defendant cannot provide compensation, failing to guarantee the compensation the victim is entitled to, as outlined in the court decision. In such cases, state involvement is required. This research aims to examine juridical implications of the legal vacuum in providing compensation in lieu of restitution. Using a normative method with statutory and analytical approaches, and grammatical and teleological interpretations, the study reveals that the absence of specific regulations leads to injustice, legal disadvantages, and legal uncertainty affecting victims of criminal offenses, particularly regarding their right to restitution.